Pandemi dan Pemenuhan Hak Anak: Studi Kasus Peran Unicef di Yaman pada Masa Covid-19 - Kusuma, Erzalina Widya; Djatmiko, Djatmiko; Rasyidah, Resa (Department of International Relations, Brawijaya University, 2021)
Covid-19 has become a pandemic that has rapidly spread throughout the world. Less than 3 months since it was discovered in China in December 2019, the Covid-19 pandemic has crippled the world economy and caused the delivery of humanitarian aid to Yemen to be hampered due to the Covid-19 outbreak. In addition, there are still wars that cause damage to health facilities. The war, the Covid-19 epidemic and Cholera disease are adding to the devastating effects on growing children in Yemen. UNICEF, as an IGO that focuses on children, reports that in 2020 there were around 34 incidents that made these children victims of child abuse and attacks on educational facilities. This research describes the role of UNICEF in Yemen from 2019 to 2020 in fulfilling children’s rights due to 3 disasters, namely Covid-19, conflict and cholera that occurred in Yemen. This research uses the theory of the role of international organizations as aid providers which is manifested in the form of Humanitarian Assistance. This type of research is a descriptive study that uses data collection techniques in the form of literature studies from 2019 to 2020 sourced from reports from The UNICEF, the WHO website, the UN website, and various verified mass media. UNICEF's role in the form of Humanitarian Assistance is manifested in 5 programs: education, child protection, nutrition, health and sanitation. Keywords: UNICEF, Yemen, Humanitarian Assistance, Covid-19 Pandemic, Children's Rights.